The effect of taxpayer awareness on personal tax compliance with the willingness to pay tax as a mediation variable - Sitawati, Riana; Subarka, Jonas (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The goal of this study is to examine how personal tax compliance, as mediated by willingness to pay taxes, is affected by taxpayer awareness. 10,661 individual taxpayers who were enrolled with the Central Semarang Two Primary Tax Office made up the study's population. This approach to research is quantitative. The sample for this study, calculated using the Slovin formula, consisted of 100 respondents. Partial Least Square (PLS) data analysis revealed a positive relationship between taxpayer awareness and willingness to pay tax, willingness to pay tax has a positive relationship with taxpayer compliance, and individual taxpayer compliance is positively impacted by taxpayer awareness. Additionally, the impact of individual taxpayer compliance on taxpayer awareness is impacted by willingness to pay taxes.